2022
DOI: 10.3390/organoids1020011
|View full text |Cite
|
Sign up to set email alerts
|

Articular Tissue-Mimicking Organoids Derived from Mesenchymal Stem Cells and Induced Pluripotent Stem Cells

Abstract: Organoids offer a promising strategy for articular tissue regeneration, joint disease modeling, and development of precision medicine. In this study, two types of human stem cells—primary mesenchymal stem cells (MSCs) and induced pluripotent stem cells (iPSCs)—were employed to engineer organoids that mimicked bone, cartilage and adipose tissue, three key tissue components in articular joints. Prior to organoidogenesis, the iPSCs were first induced into mesenchymal progenitor cells (iMPCs). After characterizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Cartilage organoids are specific three-dimensional and functional cartilage-like tissues through self-assembled reconstruction of chondrocytes or chondroprogenitor cells ( Irie et al, 2008 ; Schon et al, 2017 ; Gryadunova et al, 2021 ), which is of essential clinical significance for tremendous translational applications to repair various cartilaginous structures throughout the body, as well as organoid biobanking, disease modeling, drug toxicity testing, personalized regenerative therapy, host–microbe interaction studies, and omics analysis (including transcriptomics, proteomics, epigenomics, and metabolomics) ( Dutta et al, 2017 ). Cartilage organoids have been successfully generated both from induced pluripotent stem cells or mesenchymal stem cells ( Li Z. et al, 2022 ). Cartilage organoid formation and their assembly into neo-hyaline-cartilage have paved a new way for large scale cartilage regeneration such as for entire joint surfaces ( Crispim and Ito, 2021 ).…”
Section: Advancements Of Cartilage Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage organoids are specific three-dimensional and functional cartilage-like tissues through self-assembled reconstruction of chondrocytes or chondroprogenitor cells ( Irie et al, 2008 ; Schon et al, 2017 ; Gryadunova et al, 2021 ), which is of essential clinical significance for tremendous translational applications to repair various cartilaginous structures throughout the body, as well as organoid biobanking, disease modeling, drug toxicity testing, personalized regenerative therapy, host–microbe interaction studies, and omics analysis (including transcriptomics, proteomics, epigenomics, and metabolomics) ( Dutta et al, 2017 ). Cartilage organoids have been successfully generated both from induced pluripotent stem cells or mesenchymal stem cells ( Li Z. et al, 2022 ). Cartilage organoid formation and their assembly into neo-hyaline-cartilage have paved a new way for large scale cartilage regeneration such as for entire joint surfaces ( Crispim and Ito, 2021 ).…”
Section: Advancements Of Cartilage Organoidsmentioning
confidence: 99%
“…Notably, increasing evidence has demonstrated critical involvements of GPCRs during development and tissue homeostasis and regeneration in various tissue and organ systems ( Luo et al, 2009 ; Cui et al, 2014 ; Feng et al, 2019 ; Montgomery et al, 2019 ; d'Aldebert et al, 2020 ; Lee et al, 2021 ; Li et al, 2022 ; Khedgikar et al, 2022 ). Crucial involvements of GPCRs, such as LGR5, in both embryonic joint development ( Feng et al, 2019 ), and postnatal joint development in juvenile mammals ( Zhou et al, 2018 ), as well as progression of arthritis development ( Li R. et al, 2022 ), have been identified, suggesting targeted modulation of GPCRs on cartilage as potential novel therapeutics for arthritis management.…”
Section: Involvements Of Gpcrs In Joint Embryogenesis and Cartilage P...mentioning
confidence: 99%
“…Subsequently, hydroxyapatite nanorods, known for their high osteoconductive properties, were added to facilitate osteogenesis. [113] Maintaining optimal temperature, pH, and oxygen levels is paramount for creating a conducive environment for the successful development of joint organoids. For example, Xie et al utilized a cartilage medium composed of dulbecco's modified eagle medium supplemented with 1% sodium pyruvate, 1% insulintransferrin-selenium, dexamethasone, ascorbic acid, and TGF-𝛽3, cultured in a 5% CO 2 incubator at 37 °C.…”
Section: Culture Condition Of 3d Bioprinted Joint Organoidsmentioning
confidence: 99%
“…[15] Li et al successfully created osteochondral organoids derived from iPSCs, featuring a bone core and a cartilage shell, through the use of osteoinductive bioceramic nanoparticles (Figure 9e). [113] For instance, Abe et al have differentiated iPSCs derived from crab-eating monkeys into chondrocytes to develop cartilage organoids (cyiPS-Cart). They then transplanted these cyiPS-Cart in an allogeneic manner to repair the cartilage of crab-eating monkeys and successfully promoted the regeneration of articular cartilage (Figure 7g).…”
Section: Basic Joint Organoidsmentioning
confidence: 99%
See 1 more Smart Citation